2018
DOI: 10.1103/physrevlett.120.156804
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Mediated Phonon-Phonon Coupling Drives the Vibrational Relaxation of CO on Cu(100)

Abstract: We bring forth a consistent theory for the electron-mediated vibrational intermode coupling that clarifies the microscopic mechanism behind the vibrational relaxation of adsorbates on metal surfaces. Our analysis points out the inability of state-of-the-art nonadiabatic theories to quantitatively reproduce the experimental linewidth of the CO internal stretch mode on Cu(100) and it emphasizes the crucial role of the electron-mediated phonon-phonon coupling in this regard. The results demonstrate a strong elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 65 publications
2
38
0
Order By: Relevance
“…It has been found that two distinct processes give rise to these changes: electron-hole pair excitations result in the frequency shifts, while electron-mediated vibrational mode coupling gives rise to linewidth changes. Since the electron temperature affects the electron-hole pair excitations and the electron-mediated vibrational mode coupling depends on both electron and phonon temperatures [447], the electron and phonon temperatures play an important role in laser-induced ultrafast dynamics.…”
Section: Laser-induced Ultrafast Adsorption Dynamics Of Molecules On mentioning
confidence: 99%
“…It has been found that two distinct processes give rise to these changes: electron-hole pair excitations result in the frequency shifts, while electron-mediated vibrational mode coupling gives rise to linewidth changes. Since the electron temperature affects the electron-hole pair excitations and the electron-mediated vibrational mode coupling depends on both electron and phonon temperatures [447], the electron and phonon temperatures play an important role in laser-induced ultrafast dynamics.…”
Section: Laser-induced Ultrafast Adsorption Dynamics Of Molecules On mentioning
confidence: 99%
“…This nonadiabatic energy dissipation mechanism has been characterized by various theoretical models, [8][9][10][11][12][13][14][15][16][17][18] cumulating with the latest first-principles calculations that quantitatively reproduced the observed lifetime. [19,20] It was thus a surprise when Shirhatti et al reported a long lifetime (~10 2 ps) for trapped CO(ν=1) in the scattering of vibrationally excited CO(ν=2) from Au (111).[21] It was postulated that physisorption might be involved, given the relatively low desorption temperature of CO from Au (111).[22] Indeed, a recent density functional theory (DFT) study by Lončarić et al did find such a physisorption well for CO on Au(111),[23] using the Bayesian Error Estimation Functional method with van der Waals corrections (BEEF-vdW).[24] The lifetime of physisorbed CO(ν=1) was calculated within first-principles many-body perturbation theory and found to be consistent with the experimental value.[21] The long vibrational lifetime was attributed to the weaker couplings with EHPs because of the large distance between the adsorbate and surface. The same argument has also been used to explain the vibrationally hot precursor CH4 on the Ir(111) surface.…”
mentioning
confidence: 99%
“…These two features are known to be instrumental for explaining the long wavelength part of the phonon spectrum in metallic bulk systems [21,23,25,26]. The processes behind π [1] ν depend on the electron distribution, while π [2] ν depends on both electron and phonon distributions [19]. In our theory, the first-and second-order contributions depend indirectly on time via the electron T e (t) and lattice T l (t) temperatures describing the excited electron and phonon distributions.…”
mentioning
confidence: 85%
“…The former term accounts for electron-hole pair excitation processes [20] including nonthermal charge transfer to unoccupied states (e.g., antibonding CO states). The latter term is responsible for the EMPPC [19]. These two features are known to be instrumental for explaining the long wavelength part of the phonon spectrum in metallic bulk systems [21,23,25,26].…”
mentioning
confidence: 97%
See 1 more Smart Citation